The Luminous Manifestations and Their Symbolic Significance in Ibn Arabi's 'Tarjuman al-Ashwaq'"*: An Artistic Semantic Study - Dhurgham Muhammad Ridha Ali Al-Obaid, Lct. Dr. (Wasit Journal for Human Sciences, 2025)
constitute a fundamental axis around which the spiritual states (*ahwāl*) and stations (*maqāmāt*) of Sufis revolve. They are the pivotal center of their rituals and devotions, serving as both the primary impetus for these practices and the ultimate aspiration sought by the Sufi. The celestial bodies—the sun, moon, and stars—along with lightning and the radiance of the heavens, represent the most significant forms of the Divine Essence’s manifestations, embodying splendor, light, brilliance, elevation, luminosity, and transcendence, as well as awe and illumination. The poetic works *Tarjumān al-Ashwāq* (*The Interpreter of Desires*) and *Dhakhā’ir al-A‘lāq* (*Treasures of Precious Love*) by Ibn ‘Arabī abound with poetic testimonies to these manifestations, reflecting the Sufi’s religious and epistemological philosophy while portraying the state of the Sufi lover in his yearning for the Sacred Divine. Metaphors, similes, and symbols abound—light becomes a metaphor for divine emanation, the sun a manifestation of Truth, interwoven with other Sufi symbols, collectively shaping artistic poetic texts. From an analysis of the concept of Sufi Manifestation (*Tajallī*) in the aforementioned texts, several conclusions can be drawn:
Keywords: Keywords : The Sun , Lights , Manifestations , Divine Love Tarjumān al-Ashwāq , A Hermeneutical